Gut microbiome changes in mouse, Mongolian gerbil, and hamster models following Clostridioides difficile challenge - Wan, Shuangshuang; You, Peijun; Shi, Qikai; Hu, Hui; Zhang, Lu; Chen, Leyang; Wu, Ziyi; Lin, Shan; Song, Xiaojun; Luo, Yongneng; Wang, Yaxuan; Ju, Feng; et al. (Frontiers in Microbiology, 2024)
Clostridioides difficile infection (CDI), as well as its etiology and pathogenesis, have been extensively investigated. However, the absence of suitable CDI animal models that reflect CDI symptoms and the associated gut microbiome changes in humans has limited research progress in this field. In this study, we aimed to investigate whether Mongolian gerbils, which present a range of human pathological conditions, can been used in studies on CDI. Thus, we infected Mongolian gerbils and two existing CDI model animals, mice and hamsters, with the hypervirulent ribotype 027 C. difficile strain, and comparatively analyzed changes in their gut microbiome composition via 16S rRNA gene sequencing. The results obtained showed that C. difficile colonized the gastrointestinal tracts of the three rodents, and after the C. difficile challenge, C57BL/6J mice did not manifest CDI symptoms and their intestines showed no significant pathological changes. However, the hamsters showed explosive intestinal bleeding and inflammation and the Mongolian gerbils presented diarrhea as well as increased infiltration of inflammatory cells, mucus secretion, and epithelial cell shedding in their intestinal tissue. Further, intestinal microbiome analysis revealed significant differences with respect to intestinal flora abundance and diversity. Specifically, after C. difficile challenge, the Firmicutes/Bacteroidetes ratio decreased for C57BL/6J mice, but increased significantly for Mongolian gerbils and hamsters. Furthermore, the abundance of Proteobacteria increased in all three models, especially in hamsters, while that of Verrucomicrobia only increased significantly in C57BL/6J mice and Mongolian gerbils. Our results also indicated that differences in the relative abundances of Lactobacillaceae and Akkermansia were primarily responsible for the observed differences in response to C. difficile challenge. Therefore, based on the observed responses to C. difficile challenge, we concluded for the first time that the Mongolian gerbil could be used as an animal model for CDI. Additionally, the taxa identified in this study may be used as biomarkers for further studies on CDI and to improve understanding regarding changes in gut microbiome in CDI-related diseases.